Factors affecting the role of canonical Wnt inhibitor Dickkopf-1 in cancer progression - Doucet, Dakota; Brubaker, Connor; Turner, Donald; Gregory, Carl A. (Frontiers in Oncology, 2023)
Background: The canonical Wnt inhibitor Dickkopf-1 (Dkk-1) has the capacity to modulate homeostasis between canonical and non-canonical Wnt pathways and also signal independently of Wnt. The specific effects of Dkk-1 activity on tumor physiology are therefore unpredictable with examples of Dkk-1 serving as either a driver or suppressor of malignancy. Given that Dkk-1 blockade may serve as a potential treatment for some types of cancer, we questioned whether it is possible to predict the role of Dkk-1 on tumor progression based on the tissue origin of the tumor. Methods: Original research articles that described Dkk-1 in terms a tumor suppressor or driver of cancer growth were identified. To determine the association between tumor developmental origin and the role of Dkk-1, a logistic regression was performed. The Cancer Genome Atlas database was interrogated for survival statistics based on tumor Dkk-1 expression. Results: We report that Dkk-1 is statistically more likely to serve as a suppressor in tumors arising from the ectoderm (p = 0.0198) or endoderm (p = 0.0334) but more likely to serve as a disease driver in tumors of mesodermal origin (p = 0.0155). Survival analyses indicated that in cases where Dkk-1 expression could be stratified, high Dkk-1 expression is usually associated with poor prognosis. This in part may be due to pro-tumorigenic role Dkk-1 plays on tumor cells but also through its influence on immunomodulatory and angiogenic processes in the tumor stroma. Conclusion: Dkk-1 has a context-specific dual role as a tumor suppressor or driver. Dkk-1 was significantly more likely to serve as a tumor suppressor in tumors arising from ectoderm and endoderm while the converse was true for mesodermal tumors. Patient survival data indicated high Dkk-1 expression was generally a poor prognostic indicator. These findings provide further support for the importance of Dkk-1 as a therapeutic cancer target in some cases.